A CONCORDÂNCIA VERBAL COM A PRIMEIRA PESSOA DO PLURAL EM PANAMBI E PORTO ALEGRE, RS - Zilles, Ana Maria Stahl; Maya, Leonardo Zechlinski; da Silva, Karine Quadros (Organon, 2012)
This is part of a project about several related morphosyntactic changesin Brazilian Portuguese using data from VARSUL data base. Two cities in RS areconsidered: Porto Alegre, the capital, and Panambi, a bilingual community. Thesample included 32 interviews stratified according to sex, age, and level of formaleducation. The variable investigated is verbal marking with first person pluralsubjects. The variants are: standard agreement (-mos ending) and twononstandard forms: zero and /s/ deleted -mo inflections. Supposing two differentvariable rules, we made three separate Varbrul analyses: a)contrasting the threevariants; b) contrasting zero inflection with both -mos and -mo endings takentogether; and c)contrasting only -mos and -mo endings. The distribution of thevariants was: 53% of standard tokens, 34% of -mo endings and only 13% of zeroinflection. Results showed different factor groups associated with zero inflectionand nonstandard -mo inflection, supporting the idea of having two separatevariable rules. The level of formal education turned out to be the only significantfactor group in common for both nonstandard forms. It was also highlighted in thethree-way comparison. Zero inflection was favoured only when the target wordhad antepenultimate stress, suggesting avoidance of this stress pattern. Thebilingual community had an effect only on zero inflection.